Effect of Fetal Calf Serum (FCS) Versus Polyvinylpyrrolidine (PVP) on in vitro Maturation of Oocytes Retrieved by Ovum Pick-up (OPU) in Sahiwal Cows - Singh, Khushpreet; Singh, Narinder; Kaur Mavi, Gurjot; Honparkhe, Mrigank; Shekhar, Apoorva; Singh, Prahlad (The Indian Journal of Animal Reproduction, 2025)
The experiment was conducted to compare the effect of supplementation of fetal calf serum (FCS) versus polyvin ylpyrrolidine (PVP) on in vitro maturation (IVM) of the bovine oocytes collected by ovum pick-up (OPU) method. Cumulus oocyte complexes (COC’s) obtained by follicular aspiration having at least a complete layer of cumulus cells were randomly divided into two groups containing 10 replicates each of 10-12 oocytes. In vitro maturation of the COC’s supplementation of 5% FCS showed (Mean±Std. Error, %) higher full expansion of cumulus cells (9.20±0.64, 90.20) in comparison to 1% PVP (8.5±0.45, 81.73), though non-significant. On the other hand, COC’s showing intermedi ate expansion were significantly low (p<0.05) in maturation media (Mean±Std. Error, %) supplemented with 5% FCS (0.40±0.21, 3.9) in comparison to 1% PVP (1.30± 0.30, 12.50). Higher maturation rate in media supplemented with FCS might be due to growth factors, nutrients, hormones and antioxidants present in it. FCS contains number of growth fac tors that play an important role in regulation of oocyte maturation, particularly via cumulus cells. IVM media containing 5% FCS provides a favourable environment in comparison to 1% PVP for in vitro maturation of bovine oocytes obtained though ovum pick-up.